Information Engineering: Strategic decision based on data science - Martins da Rocha, Prof. Carlos Alberto; Gouveia, Prof. Dr. Luis Borges (International Journal of Advanced Engineering Research and Science, 2021)
The contemporary society of the 21st century is composed and grounded in data. This scenario was made over the years and centuries of history. The technology, however, is recent in human history and began about 400 years ago, simultaneously with the emergence of modern science. We are no longer an industrial society, but an information society. This is a conception of a new social organization, based on information technology. The Information Society is supported by the acquisition, storage, processing and distribution of information by electronic means, in Information and Communication Technologies. The interaction between individuals and institutions became predominantly digital. Up-to-date managers must make data-driven decisions. Those who are able to unite domain expertise with data science can make more accurate strategic decisions. Knowledge is linked to its context in a broader way, with social and cultural implications as well. Industry 4.0 makes it possible to gather and analyze data between machines, faster and more efficiently, thus having an effect on the competitiveness between companies and even regions, even altering the economy. Information Science is a vast growing field of research and development of solutions, including, and mainly, for Knowledge Management and Strategic Management, in decision-making by public and private institutions.